Spring Freeze–Thaw Stimulates Greenhouse Gas Emissions From Agricultural Soil - Badewa, Emmanuel A.; Yeung, Chun C.; Rezanezhad, Fereidoun; Whalen, Joann K.; Oelbermann, Maren (Frontiers in Environmental Science, 2022)
Graphical Abstract